A giant hemangioma of the sigmoid colon as a cause of lower gastrointestinal bleeding in a young man. Issue 6 (2nd November 2022) - Fair, Lucas; Gough, Benjamin; Oknokwo, Adatee; Stadler, Ronney
Abstract: Although hemangiomas are among the rarest causes of lower gastrointestinal bleeding, they should be considered in young adults with recurrent, painless gastrointestinal bleeding. We present a case report of a 37-year-old man with a 2-month history of intermittent rectal bleeding who had a single large hemangioma in the sigmoid colon, successfully treated with elective laparoscopic sigmoid resection.